Peran Guru PPKn dalam Meningkatkan Karakter Beriman Dan Bertaqwa Kepada Tuhan Yang Maha Esa Dan Berkebinekaan Global Peserta Didik Kelas X Di SMA Negeri 1 Jombang - Femas Galih Alfansyah; Firman Firman (Al-Riwayah : Jurnal Kependidikan, 2026)
Moral and character education is a process to instill noble values ​​in students through developing insight, strengthening self-understanding, firmness of attitude, and encouragement to practice these values ​​in everyday life. Problems that arise in improving the character of Faith and Piety to God Almighty are lying, cheating, bullying, envy, spreading slander, and misuse of social media, while the character of Global Diversity is less respect for friends' opinions, often interrupting conversations, forcing opinions, and tending to socialize only with friends of the same religion. This study aims to (1) describe the role of PPKn teachers in improving the character of Faith and Piety to God Almighty in Class X students at SMA Negeri 1 Jombang and (2) describe the role of PPKn teachers in improving the character of Global Diversity in Class X students at SMA Negeri 1 Jombang. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation, as well as data analysis which includes collection, reduction, presentation, and drawing conclusions. The results of this study indicate that: (1) PPKn teachers improve the character of faith and piety towards God Almighty through: obedience to worship, sincerity in prayer, love for holy books, and noble morals. (2) PPKn teachers improve the character of global diversity through: respecting different cultures, interacting and collaborating together and caring for and preserving culture.